2018
DOI: 10.19080/jpfmts.2018.02.555592
|View full text |Cite
|
Sign up to set email alerts
|

Activity Profile between Winners and Losers ¡j in International Silat Olahraga Matches

Abstract: Material and Methods Match AnalysisThe Silat Olahraga SEA Games 2015 videos, which publicly available online were used in analysis. Nineteen (19) Silat Olahraga matches in SEA Games 2015 were selected in this study. These videos were male and female quarterfinals, semifinal, and final matches. Each category emphasis of different class, start from class A (45-50 kg), class B (50-55 kg), class C (55-60 kg), class D (60-65 kg), class E (65-70 kg), class F (70-75 kg), class G (75-80 kg), and class H (80-85kg). For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In silat, any legal/clear points (HT) with a punch (1 point), kick (2 points) or topple down (3 points) will help the athlete to increase his/her score (Anuar, 1992). Shapie et al (2018a) reported that the winners from 19 matches in international silat matches performed more actions than the losers. Secondly, this study showed that the most frequent successful action performed by the winners was kick.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In silat, any legal/clear points (HT) with a punch (1 point), kick (2 points) or topple down (3 points) will help the athlete to increase his/her score (Anuar, 1992). Shapie et al (2018a) reported that the winners from 19 matches in international silat matches performed more actions than the losers. Secondly, this study showed that the most frequent successful action performed by the winners was kick.…”
Section: Discussionmentioning
confidence: 99%
“…Tempur means combat, sparring or battle between exponents (Shapie et al, 2019). This combative sport focuses on young exponents, particularly beginners (Shapie et al, 2018a). The main agenda of this sport is to improve combative techniques performed by young silat exponents in competition (Shapie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the silat matches were played using Nacsport Elite (sports performance analysis software), which allows to pause and play back frame-by-frame for ease of use. For this study, 14 different types of motion categories were coded, including kick, punch, block, catch, topple, sweep, evade/dodge, self-release, block and punch, block and kick, block and sweep, fake punch, fake kick and others (Shapie et al, 2018). The motion categories were divided into three outcomes, which were Hit Target (HT), Hit Elsewhere (HE) and Missing Opponent (MO).…”
Section: Methodsmentioning
confidence: 99%